Pengaruh Growth, Earning Per Share dan Profitabilitas Terhadap Kebijakan Dividen: Studi Empiris pada Perusahaan Non Keuangan - Gibralthar Remelko; Mia Angelina Setiawan (Universitas Negeri Padang, 2021)
This study purpose to examine how the effect of Growth, Earnings Per Share, and profitability on Dividend Policy. The population in this study are non-financial companies listed on the Indonesia Stock Exchange in 2015-2019. This research technique uses purposive sampling technique to obtain research samples. The data analysis technique in this study used multiple linear regression analysis using the SPSS 22 program. The results showed that Growth had no effect on Dividend Policy while Earning per share and Profitability had a significant and significant effect on Dividend Policy. For further research, it is expected to choose other variables that have an effect on Dividend Policy.